2009
DOI: 10.1051/0004-6361/200912272
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent resistivity evaluation in magnetorotational instability generated turbulence

Abstract: Context. MRI turbulence is a leading mechanism for the generation of an efficient turbulent transport of angular momentum in an accretion disk through a turbulent viscosity effect. It is believed that the same process could also transport large-scale magnetic fields in disks, reshaping the magnetic structures in these objects. This process, known as turbulent resistivity, has been suggested and used in several accretion-ejection models and simulations to produce jets. Still, the efficiency of MRI-driven turbul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 36 publications
12
93
1
Order By: Relevance
“…Lubow et al (1994) showed that a SAD would get rid off its magnetic field unless the turbulent viscosity is much larger than the diffusivity (precisely, P m ∼ r/h). This is kind of problematic as our current view of turbulence would suggest instead P m ∼ o(1) Lesur & Longaretti (2009). However, they did not take into account the disc vertical equilibrium and, as pointed out by Rothstein & Lovelace (2008), advection could still be occurring.…”
Section: Jeds In Lmxbsmentioning
confidence: 92%
See 1 more Smart Citation
“…Lubow et al (1994) showed that a SAD would get rid off its magnetic field unless the turbulent viscosity is much larger than the diffusivity (precisely, P m ∼ r/h). This is kind of problematic as our current view of turbulence would suggest instead P m ∼ o(1) Lesur & Longaretti (2009). However, they did not take into account the disc vertical equilibrium and, as pointed out by Rothstein & Lovelace (2008), advection could still be occurring.…”
Section: Jeds In Lmxbsmentioning
confidence: 92%
“…Whether or not 3D MHD turbulence in accretion discs can indeed be described by a local prescription is an open question. However, recent work on 3D MRI in shearing box has shown that a fully turbulent medium displays both a viscosity and a magnetic diffusivity, such that the effective magnetic Prandtl number lies between 2 and 5 (Lesur & Longaretti 2009). Moreover, the functional dependency of the transport coefficients on the magnetic field is the same as the one we used (ν v ∝ ν m ∝ V A h).…”
Section: Ferreiramentioning
confidence: 99%
“…Therefore, strongly inclined fields would be possible only for a magnetic Prandtl number P m = ⌫ v /⌫ m ⇠ r/h [32]. However, our current understanding of (and conventional wisdom on) MHD turbulence favors P m around unity [33,34]. Thus, according to this simple argument, any large scale B z field would just di↵use outwardly in a thin accretion disc.…”
Section: Bp Versus Bz Jets: Jeds Vs Mads ?mentioning
confidence: 93%
“…In order to compress all the open flux in a small region around corotation ("flux-trapping", in the X-wind jargon), the X-wind magnetic configuration requires a magnetic Prandtl number, given by the ratio between the disk (turbulent) viscosity and magnetic diffusivity, of order r/h 1. Our current knowledge about MRI-driven turbulence in accretion disks seems to favor magnetic Prandtl number values around unity [38]. Over such a small radial extent, the accretion disk does not contain enough mechanical energy to fuel an outflow with the typical characteristics of an X-wind, but it can launch a less massive/powerful outflow only.…”
Section: Disk Windsmentioning
confidence: 99%